Skin cancers in skin types IV-VI: Does the Fitzpatrick scale give a false sense of security? - P. Goon; C. Banfield; O. Bello; N. J. Levell (Wiley, 2021)
Abstract The Fitzpatrick scale has been in use for skin colour typing according to the tanning potential of skin since its inception in 1975-1976. Thomas Fitzpatrick developed the scale to classify persons with 'white skin' in order to select the correct amount of UVA in Joules/cm2 for PUVA treatment for psoriasis. Since then, it has been widely used in Dermatology to gauge the skin's reaction to UV exposure, tanning potential, assessment of sunburn risk and amount of sun protection required for individual patients. However, the use of this scale has been of limited utility because of different self‐perception in different areas of the world, particularly among those with skin of colour. Skin cancer risk is loosely inversely correlated with the initial genetic/inherent amount of melanin (most research has focused on eumelanin) present in the skin, although the pattern of exposure and amount of UV radiation required causing DNA damage varies widely according to different cancers. In this review, we have shown that the Fitzpatrick scale is neither correct nor adequate to reflect sunburn and tanning risk for skin of colour. Therefore, it may give both patients and physicians a false sense of security that there is little risk that people of colour can develop skin cancers. We have reviewed the small but not insignificant risk of skin of colour developing skin cancers and emphasise that there remains much research that needs to be done in this field.